Factors Influence Intention to Opt for Islamic Investment Schemes among Market Players - Muhammad Abduh (Global Review of Islamic Economics and Business, 2017)
Employing theory of reasoned action with religiosity as its additional construct in the model, this paper is aimed at examining factors influence the intention of investors to opt Islamic investment schemes in Malaysia Islamic capital markets. As many as 120 questionnaires were collected from market players in Bursa Malaysia using online survey. Afterwards, the data collected were analyzed using structural equation model to reveal the relationship of variables tested in the proposed model. The result shows that religiosity and subjective norms appeared to be the significant factors affecting intention to choose Islamic investment schemes in Malaysia Islamic capital markets. Interestingly, despite its significant role shown in previous studies, this study has shown insignificant level of the attitude in predicting the intention behavior. The managerial implications are discussed in this paper. Keywords: Investors’ behavior, Islamic investment, Bursa Malaysia